Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon - Hernández-García, Luis Manuel; Burgos-Guerrero, Jesús Enrique; Santos, Bianca Tamires Silva Dos; Rousseau, Guillaume Xavier; James, Samuel Wooster (Zootaxa, 2018)
We describe three new species of the earthworm genus Holoscolex from the Gurupi Biological Reserve in Maranhão state, Brazil. The Reserve, with the Indigenous Territories Awá, Caru, Alto Turiaçu and Alto Rio Guamá represent the last continuous forest remnants of the Belém Endemism Area, the most deforested and threatened area of Brazilian Amazonia. Holoscolex dossantosi sp. nov. has tubercula pubertatis looking like double bands, Holoscolex alatus sp. nov. presents alate tubercula pubertatis, and Holoscolex fernandoi sp. nov. has testis sacs and several intraclitellar atrial glands associated with genital markings between XIX and XXII. The presence of these unusual characters in Holoscolex fernandoi sp. nov. suggests that this species could be an evolutionary transitional stage linking Eudrilidae and more recent Glossoscolecidae genera.